Pedagogical interaction in the context of humanization of education - Мельник, Ірина Миколаївна; Melnyk, Iryna M.; Кудрик, Валентина Володимирівна; Kudryk, Valentyna V. (PSW im. Papieża Jana Pawła II w Białe Podlaskiej, 2014)
The article deals with the problem of pedagogical interaction, its potential in educational and upbringing processes directed to humanization of relations between teacher and pupils. On the basis of analysis of the research it can be concluded that pedagogical science operates with a conception of pedagogical interaction, that is considered to be one of the principal categories of pedagogics. It has to be emphasized thatthe conception “interaction” in general understanding reflects the universal general form of movement and influence of objects at each other. For man it is their characteristic aspiration in the interaction with different objects of the surrounding world. Through the interaction men learns about natural and social phenomena, conform to law, processes and determine the methods of their thinking andbehaviour. Men’s need in communication, studying, education and his own development are connected with this concept.
Keywords: pedagogical interaction; collaboration; humanization of relations in schools; pedagogiczne współdziałanie; współpraca; humanizacja w relacjach